(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
A simple, rapid and economic UV spectrophotometric method has been developed and validated using a solvent 0.1N HCl to determine Dextromethorphan hydrobromide content in bulk and two different pharmaceutical solid dosage formulations, lozenges and chewable tablets. At the pre-determined λmax of 278 nm, it was proved linear in the range of 5.0-30.0 µg/ml and exhibited good correlation coefficient (R2=0.9993) and excellent mean recovery (101.37-100.76%) and (100.66-101.17%) for lozenges and chewable tablets respectively. This method was successfully applied to the determination of Dextromethorphan hydrobromide content in lozenges and chewable tablets and the results were in good agreement with the label claim. The method was validated as per ICH guidelines for linearity, precision, accuracy, specificity, LOD and LOQ. The obtained results proved that the method can be employed for the routine analysis of Dextromethorphan hydrobromide in bulks as well as in the pharmaceutical formulations.